Basic Strategies and Types of Applications in Organic Electrochemistry - Hilt, Gerhard (ChemElectroChem, 2020)
The outlook of this paper is to give a short overview of the basic requirements to perform electro‐organic transformations. The aim is to explain the strategies and possible applications in organic electrochemistry as simply as possible and is directed to those scientists who are not necessarily trained electrochemists and those that intend to utilize this powerful and, nowadays, very popular tool in their research. Different types of electrolysis performed in a galvanostatic/potentiostatic/alternating current fashion will be presented and the strategies to perform divided/undivided/quasi‐divided electrolysis will be covered. The application of direct/indirect/cation‐pool electrolysis as well as several variants of paired electrolysis will be briefly explained utilizing selected examples. Beginners guide: The basic principles for performing electrolysis in organic chemistry under galvanostatic/potentiostatic conditions in undivided/divided/quasi‐divided cell designs via direct or indirect electrochemical electron transfer reactions are exemplified at selected examples, including those where paired electrolysis has been used to utilize both electrode reactions in a productive fashion.